Clinical evaluation of an ointment with 10% metronidazole and 2% lidocaine in the treatment of alveolitis. - Silva, L. J.; Poi, Wilson Roberto [UNESP]; Barioni, Sônia Regina Panzarini [UNESP]; Rodrigues, T. S.; Simonato, L. E. (My University, 2006)
AIM: In this study, the authors evaluate the use of a 10% metronidazole and 2% lidocaine ointment, using a lanolin base and mint as flavoring, to treat alveolitis in humans. METHODS: Twenty-five patients, with a diagnosis of alveolitis, were treated in the following way: locoregional anesthesia; surgical cleaning of the socket with alveolar curettes; saline solution irrigation with a 20 ml disposable syringe; and complete filling of the socket with the ointment. RESULTS: The analysis of the results showed that the painful symptoms were severe before and on the day of the treatment in 17 (68%) of the 25 patients treated. Post-treatment analysis presented 2 patients (18%) with severe painful symptoms after 24 h of the treatment and complete remission of painful symptoms after 48 h of the treatment with the ointment. CONCLUSIONS: Based on the results, it is possible to conclude that the 10% metronidazole and 2% lidocaine ointment, with mint flavoring and lanolin as a base, can be used to treat alveolitis.
Keywords: antiinfective agent; lidocaine; local anesthetic agent; metronidazole; adolescent; adult; clinical trial; drug combination; female; human; male; middle aged; ointment; tooth pain; Adolescent; Adult; Anesthetics, Local; Anti-Infective Agents; Drug Combinations; Dry Socket; Female; Humans; Lidocaine; Male; Metronidazole; Middle Aged; Ointments